A core-shell Mn–C@Fe nanocatalyst under ozone activation for efficient organic degradation: Surface-mediated non-radical oxidation. (October 2021) - Guo, Ziyi; Zhang, Yuan; Wang, Dong
Abstract: A non-radical catalytic ozonation process functionalized by Mn(II)-sites was found effective to degrade oxalic acid as a typical refractory compound that is hard to remove through catalytic ozonation with hydroxyl radical oxidation. Specifically, we prepared functional Mn–C@Fe nanoparticles with carbon shell supporting Mn3 O4 for catalysis while encapsulating magnetic iron core for recycle. Batch study shows its excellent catalytic reactivity on the degradation of organics particular for the ozone-recalcitrant oxalic acid (20 min for 90.9% removal, kinetics constant of 0.045 min −1 ). Our mechanism study ruled out the hydroxyl radical oxidation, and highlighted the formation of a heptavalent Mn intermediate oxidant responsible for the fast degradation that was initiated via ozone activation of Mn(II)-sites on the carbon shell. Our findings underscore a non-radical catalytic ozonation as a promising alternative technology for the abatement of aqueous organic pollutants. Graphical abstract: Image 1 Highlights: Ozone activation of Mn–C@Fe catalyst exhibited fast removal of oxalic acid. Non-radical chain reactions were induced by ozonation of unsaturated Mn(II)-sites. Multiple organics degradation were achieved even with hydroxyl radical quencher. Mn–C@Fe core-shell structure allows for a facile reclaim, regeneration, and reuse.